Investigation of The Factors Affecting The Banking Preferences of Public Employees Using Advertisements Through Mixed Method - Yalçın Karagöz; Kasım Can Işık (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
In this study, exploratory survey design, which is one of the mixed methods, was used to determine the factors affecting the banking preferences of the public employees. 36 commercials of 9 banks broadcast on television were used as qualitative data. These commercials were examined with NVivo 10 package program in terms of factors affecting the banking preference of public employees. In the qualitative analysis, 83 codes and 6 themes were obtained. The 83 codes obtained were used for the item pool of the scale. 6 themes were determined as the factors of the scale. The draft scale was administered to 400 public employees working in Sivas province by using stratified sampling method. Based on the data obtained, a measurement tool consisting of 6 factors and 26 items was developed by using SPSS and AMOS package programs. As a result, the relationships between the banking preference criteria and demographic variables of the public employees in Sivas were evaluated by statistical methods and the differences were interpreted.